Development and Comparative Evaluation of Machine Learning Models using Clinically Relevant Features for Predicting Newborn Patients’ Length of Stay - Gandung Triyono; Billy Marentek; Mohammad Syafrullah (Informatika, Universitas Jenderal Soedirman, 2026)
The Length of Stay (LOS) of newborns is a crucial indicator for healthcare management and hospital resource allocation. However, prior research has yet to systematically compare machine learning models for newborn LOS prediction using clinically pertinent features in developing-country hospital contexts, creating an important methodological and contextual gap. Accurate prediction of LOS is urgently needed to support timely clinical decision-making and prevent overcrowding, inefficiencies, and unnecessary healthcare costs. This study aims to identify factors influencing LOS and develop a predictive model for newborn LOS using several machine learning algorithms. A comparison was conducted among Linear Regression, Random Forest Regression, Support Vector Regression (SVR), and Artificial Neural Networks (ANN). The dataset consisted of medical records of newborn patients from three private hospitals in Indonesia. The research included data collection and understanding, data preprocessing, modeling, and evaluation. Experimental results show that Random Forest Regression achieved the best predictive performance, with MAE = 0.019, MSE = 0.011, RMSE = 0.086, and R² = 0.987. Feature importance analysis revealed that gender, referral source, insurance type, and diagnosis were the most influential predictors of LOS. This study contributes to the advancement of machine learning applications in healthcare data analytics and provides evidence-based insights to support neonatal care planning and hospital resource optimization.